2014
DOI: 10.3390/md12021131
|View full text |Cite
|
Sign up to set email alerts
|

The Marine Sponge-Derived Inorganic Polymers, Biosilica and Polyphosphate, as Morphogenetically Active Matrices/Scaffolds for the Differentiation of Human Multipotent Stromal Cells: Potential Application in 3D Printing and Distraction Osteogenesis

Abstract: The two marine inorganic polymers, biosilica (BS), enzymatically synthesized from ortho-silicate, and polyphosphate (polyP), a likewise enzymatically synthesized polymer consisting of 10 to >100 phosphate residues linked by high-energy phosphoanhydride bonds, have previously been shown to display a morphogenetic effect on osteoblasts. In the present study, the effect of these polymers on the differential differentiation of human multipotent stromal cells (hMSC), mesenchymal stem cells, that had been encapsulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 44 publications
(68 reference statements)
1
45
0
2
Order By: Relevance
“…Thus in our experiment, cells did not develop multicellular clusters, typical for osteogenic differentiation of cellular monolayer as observed by us and others [1, 22, 23], but were evenly dispersed. We decided to immobilize cells at low concentration to avoid the cell clustering process, so we could analyze the osteogenic differentiation of single cells.…”
Section: Discussionsupporting
confidence: 78%
“…Thus in our experiment, cells did not develop multicellular clusters, typical for osteogenic differentiation of cellular monolayer as observed by us and others [1, 22, 23], but were evenly dispersed. We decided to immobilize cells at low concentration to avoid the cell clustering process, so we could analyze the osteogenic differentiation of single cells.…”
Section: Discussionsupporting
confidence: 78%
“…6,[34][35][36] PolyP-mediated modulation of osteoblast-specific gene expression has been studied in MC3T3E1, SaOS2 and MSCs. 20,34,37,38 To the best of our knowledge, there were no reports available to support the role of Pg and its composite scaffolds in bone formation. In this study, we developed CS-based scaffolds and tested the components, CaPP and Pg particles, for their ability to promote bone formation in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…). In addition to those studies with polyP in the nanoparticle application form, it has been demonstrated that Na‐polyP, complexed with Ca 2+ in solution, causes an osteogenic differentiation of human multipotent stromal cells as well as an expression of the genes encoding for BMP‐2 and collagen‐I …”
Section: Polyp (Nanoparticles) As a Morphogenetically Active Polymermentioning
confidence: 99%